EPS Prize Lecture. Learning to read words. - Nation, K (2008)
The ease with which we process the written word belies its complexities and makes it easy to forget that it is a highly skilled behaviour and one that takes time to master. In this paper, I argue that our ability to read words has its roots in our capacity for language. Good progress has been made towards understanding how children discover the systematic relationship between speech sounds and the letters used to represents those sounds, very early in reading development. However, we understand much less about how beginning readers become skilled readers. To understand this, I argue that it is important to view the visual word recognition system within the context of a broader language system, one that incorporates a rich network of semantic and episodic knowledge.